Lifestyle, Religiosity and the Intention of Students in Visiting the Artifacts of Islamic Civilization Museum - SUMADI, SUMADI (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.11.2(42).14, 2020)
This research aims to find out and analyze whether there is an influence of lifestyle and religiosity on the attitude and intention of Muslim students to visit the Islamic civilization artifacts museum in Indonesia. The population are students in Indonesia. Sample takes from Muslim population as Yogyakarta students which are from various regions in Indonesia that study at a University in Yogyakarta i.e Universitas Islam Indonesia, Universitas Muhammadiyah Yogyakarta and Universitas Gadjah Mada. Sample was taken by non-random sampling convenience technique. The number of samples was 166 students, using 4 research variables, namely lifestyle, religiosity, attitude and intention, and 29 question indicators. Data analyzed use AMOS 21's Structural Equation Modeling Analysis (SEM). The results showed that there was a positive and significant influence between lifestyle to attitude and intention in visiting the Islamic civilization artifacts museum. The religiosity had a positive and significant effect on the attitude, but it was not significant to the intention. The attitude had a enough role means as a variable intervening for lifestyle and religiosity towards the intention, and the attitude had a positive and significant influence on the intention of the Muslim students to visit of the Islamic civilization museum. This research limit only at student intention on the basis of personal influence, thus opening up the research from external influences. Beside of that the sample of this research only in Yogyakarta, not from others region in Indonesia. Islamic Museum Organizer can use the information about lifestyle and religiosity to be implicated in their museum product. Positive impact about lifestyle and religiosity can increase the Student intention to visit Islamic Museum. Individual backgrounds in the form of lifestyle and religiosity for attitudes toward museum object have not been studied in Indonesia, therefore researcher are interested to study this case.